2015
DOI: 10.1139/gen-2015-0035
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of theLRR-RLKgene family in tomato (Solanum lycopersicum) Heinz 1706

Abstract: As the largest subfamily of receptor-like kinases (RLKs), leucine-rich repeat receptor-like kinases (LRR-RLKs) regulate the growth, development, and stress responses of plants. Through a reiterative process of sequence analysis and re-annotation, 234 LRR-RLK genes were identified in the genome of tomato (Solanum lycopersicum) 'Heinz 1706', which were further grouped into 10 major groups based on their sequence similarity. In comparison to the significant role of tandem duplication in the expansion process of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 64 publications
7
61
0
Order By: Relevance
“…Hence, the results suggested LRR-RLK genes from different subfamilies and even genes from the same subfamilies exhibited expressional divergence. Similar results have also been obtained from the expression analyses of LRR-RLK genes from other plants (Zan et al, 2013; Rameneni et al, 2015; Wei et al, 2015; Shumayla et al, 2016; Zhou et al, 2016). …”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Hence, the results suggested LRR-RLK genes from different subfamilies and even genes from the same subfamilies exhibited expressional divergence. Similar results have also been obtained from the expression analyses of LRR-RLK genes from other plants (Zan et al, 2013; Rameneni et al, 2015; Wei et al, 2015; Shumayla et al, 2016; Zhou et al, 2016). …”
Section: Discussionsupporting
confidence: 78%
“…In this study, we focused on the number of LRR repeats in the LRR domain and motifs in the KD domain. Previous studies in eudicots and monocots reported that members within the same LRR-RLK subfamily tend to have a similar number of LRR repeats, whereas members of different subfamilies exhibit a different number of LRR repeats (Shiu and Bleecker, 2001; Sun and Wang, 2011; Zan et al, 2013; Rameneni et al, 2015; Wei et al, 2015; Magalhães et al, 2016; Shumayla et al, 2016). The protein structure analyses of LRR-RLK proteins in A. trichopoda reinforced the conclusion that the same subfamily members tend to have broadly the same number of LRR repeats in the LRR domain (Figures 3A,B and Table 1), while members of different subfamilies have different numbers of LRR repeats in the LRR domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OPE5 was expressed in ovule and seed, and Solyc03g096190 was expressed in placenta and septum (S3 Table). In tomato, the LRR-RLK family represents the largest family of RLKs [109]. Molecular genetic studies have shown that LRR-RLKs are involved in a wide range of plant development, such as stem cell maintenance [110,111], cell fate determination and patterning [103,112], and brassinosteroid signaling [113115].…”
Section: Resultsmentioning
confidence: 99%